Pedagogical Leadership in School A Qualitative Study - Bhardwaj, B.P. (JOURNAL OF INDIAN EDUCATION, 2022)
The concept of pedagogical leadership in school is relatively new that has emerged in the early 1980s and has not received much attention in the modern India. Since school is a people-based organisation, the quality of relationships among stakeholders is significant in determining the effectiveness of its functioning. The role of the principal or school head as an effective pedagogical leader improves the quality of teachers’ pedagogic styles and the engagement of students in the teaching-learning process. In this study, the two Jawahar Navodaya Vidyalayas, one located in Chandigarh and the other in Niwarsi, Kurukshetra, were randomly selected. The case study method was followed to study the quality of education. The findings of the study are useful for policymakers and Principals to develop a capacity-building programme for Principals.